Cell cycle-specific loading of condensin I is regulated by the N-terminal tail of its kleisin subunit - Shoji Tane; Keishi Shintomi; Kazuhisa Kinoshita; Yuko Tsubota; Makoto M Yoshida; Tomoko Nishiyama; Tatsuya Hirano (eLife, 2022)
Condensin I is a pentameric protein complex that plays an essential role in mitotic chromosome assembly in eukaryotic cells. Although it has been shown that condensin I loading is mitosis specific, it remains poorly understood how the robust cell cycle regulation of condensin I is achieved. Here, we set up a panel of in vitro assays to demonstrate that cell cycle-specific loading of condensin I is regulated by the N-terminal tail (N-tail) of its kleisin subunit CAP-H. Deletion of the N-tail accelerates condensin I loading and chromosome assembly in Xenopus egg mitotic extracts. Phosphorylation-deficient and phosphorylation-mimetic mutations in the CAP-H N-tail decelerate and accelerate condensin I loading, respectively. Remarkably, deletion of the N-tail enables condensin I to assemble mitotic chromosome-like structures even in interphase extracts. Together with other extract-free functional assays in vitro, our results uncover one of the multilayered mechanisms that ensure cell cycle-specific loading of condensin I onto chromosomes.